Analisis Kinerja Usaha Peternakan Ayam Broiler di Kecamatan Selebar Kota Bengkulu - Fomi, M. Fredy Dela; Reswita; Windirah, Nola; Abubaker, Tareq A. S. (Jurnal AGRISEP, 2023)
This study aims to analyze the financial performance of the broiler farm business of PT. BCD and to find out the condition of the broiler farm business of PT. BCD. The methods used in this study are the analysis of financial ratios (solvability, liquidity, and profitability) and the Altman Z-score method (safe, gray, or distressed). The study results show that the company is suspected of experiencing unfavorable financial conditions after an analysis using financial ratios (liquidity, solvability, and profitability ratios) supported by financial report data for 2019–2021. The results obtained by broiler chicken farming company PT. BCD in 2019–2021 showed very good results. The criteria are very good, indicating that the company has managed its capital, assets, profits, and debts in a way that can be sustained for the long term. The business conditions of PT. BCD are suspected of experiencing bankruptcy after analyzing the Altman Z-score method with financial report data for 2019–2021. The results stated that the company was in a safe zone (continuing), which meant that the company did not experience bankruptcy. A high Altman Z-score indicates that the company is very far from bankruptcy.